(untitled) (Research, Society and Development, 2019)
This text has as a proposal to discuss about the performance of the bachelor without pedagogical complementation as a licensee, observing if this condition results in students’ learning difficulties. A semistructured questionnaire was applied, with thirty three participating teachers, graduated in the area of human health, who participated in the courses in the health area of three institutions. The data were treated by the content analysis and the triangulation was performed for a detailed description of the phenomena. The objective of the research was to understand the academic training of the Health Courses as well as their pedagogical complementation to act as a teacher. Exploratory field research, qualitative approach to evidence the profile and the training of the teachers who work in the courses of health. Thus we highlight the most relevant premises of the results obtained in order to highlight the experiences and professional experiences of these teachers. The results showed that all professionals understand the need for training for teaching and that this training prepares and subsidizes their practice. In continuity to this research it is known that new factors will be evidenced and will certainly contribute to future policies for the implementation of pedagogical complementation courses, specifically aimed at the bachelors in health demanded by the many evidences that we have highlighted in this study.